Estado nutricional de arboles de manzano ‘anna’ durante la (2003)
Nutritional status may influence markedly the productivityof ‘Anna’ apple trees through effect of nutrient elementscomplex on development and fruit growth. Majority ofnutrient elements influence on growth and productivitydirect or indirectly as consequences of their sharing inphysiological processes. The monthly nutrient contents of‘Anna’ apple trees in leaves and fruits that grow under acidsoil in the Colombian highlands was evaluated from 16days after full bloom to the harvest time. The nutrient contentsin shoots were evaluated both before (at defoliationtime) and after (at the harvest time) the season. Iron andcopper contents in shoots were higher after than beforethe season. On the contrary, the content of the remainingminerals were higher before than after the season. Nitrogen,boron, magnesium, phosphorus and sulfur increasedtheir foliar levels from 16 to 46 days after full bloom, butdeclined after 46 days after full bloom to the harvest time.Contents of foliar calcium, manganese, and copper wereprogressively higher as the season advanced. Potassium,iron, sodium and zinc contents in leaves were oscillatoryalong the season. Fruit content of nitrogen, potassium,magnesium, phosphorus and sulfur were progressivelylower from 46 days after full bloom to the harvest time. Onthe other hand, calcium, iron and copper increased theirlevels in fruits as the season advanced. Boron and sodiumcontents in fruits were oscillatory along the season. Thispaper provides information about the nutritional status of‘Anna’ apple trees cultivated in the Colombian highlandsand the effect of mineral content in leaves and shoots onmineral content in fruits.